(untitled) (Global Journal of Medical Research, 2026)
In this article we address three different problems of "Surface Analysis" thanks to Artificial Intelligence with Neural Networks related to the diet of the person newly affected by multiple sclerosis, a diet that can be myelinating or demyelinating; the second has the objective of recognizing whether oil, or water, can be present in a site and the presumed depth; the third objective is to classify radioactive atoms, such as Plutonium, on a neutral surface, as a sort of "Identity Card". The data were collected, not on sites or authors that deal with the topic in question, but thanks to what emerges in summary form in the most common browsers, called in this work "data found on the volatile web".